2019
DOI: 10.3390/en12101822
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Step Wind Speed Forecasting Based On Ensemble Empirical Mode Decomposition, Long Short Term Memory Network and Error Correction Strategy

Abstract: It is of great significance for wind power plant to construct an accurate multi-step wind speed prediction model, especially considering its operations and grid integration. By integrating with a data pre-processing measure, a parameter optimization algorithm and error correction strategy, a novel forecasting method for multi-step wind speed in short period is put forward in this article. In the suggested measure, the EEMD (Ensemble Empirical Mode Decomposition) is applied to extract a series of IMFs (intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In addition to this outcome, 90% of the monitoring stations have subsequently been found to be under 1.5 µg/m 3 error. Huang et al [23] developed a novel forecasting method to predict multi-step short-term wind speed by adapting the ensemble empirical mode decomposition (EEMD). It has further been shown that this study's developed model, as a result, can actually enhance the capacity of wind speed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to this outcome, 90% of the monitoring stations have subsequently been found to be under 1.5 µg/m 3 error. Huang et al [23] developed a novel forecasting method to predict multi-step short-term wind speed by adapting the ensemble empirical mode decomposition (EEMD). It has further been shown that this study's developed model, as a result, can actually enhance the capacity of wind speed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accurate short-term wind speed predictions play an important role in the safety and management optimization of wind power systems. Due to fluctuations in wind speed, accurate predictions are difficult [6,7]. Currently, with point predictions of wind speed, it is impossible to eliminate forecast errors.…”
Section: Introductionmentioning
confidence: 99%
“…WSP is directly related to the characteristics of original data, data processing methods and data prediction models. In recent years, research reports on WSP is divided into four main categories [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%